Magnetoresistance studies of two-dimensional Fe3GeTe2 nano-flake. (24th August 2022) - Zeng, Xiangyu; Ye, Ge; Huang, Shuyi; Zhang, Liang; Xu, Hongsheng; Liu, Yulu; Kuang, Haoze; Ma, Boyang; Luo, Jikui; Lu, Xin; Wang, Xiaozhi
Abstract: The magneto-transport properties of two-dimensional (2D) Fe3 GeTe2 (FGT) nano-flakes are carefully investigated with the variation of the temperature and the direction of the applied magnetic field ( B ). Four magnetoresistance (MR) behavior are obtained at different temperatures with B paralleling the flake's surface, because of the competition between the merging of different domains, spin fluctuation, and the spin momentum flipping. Different from the reported negative MR of bulk FGT, 2D FGT shows a positive MR behavior with the increase of B at a low temperature in a low B range, owning to the domination of the spin momentum flipping induced by the weakening of the coupling between different layers with the decrease of the thickness of the FGT flake. The angle-dependence of the FGT MR is also investigated and can be well explained by the competition mentioned above.